Two-dimensional superlattice nanocatalysts unlock multimodal energy transformation-driven catalytic therapy - Shanshan Zhang; Xiangyu Kong; Ximo Xu; Qing Hua; Wenwen Xu; Liang Chen; Jianqiao Zhou; Yu Chen (Nature Communications)
Abstract While the development of nanochemistry has spurred the emergence of catalytic nanomedicine, nanocatalysts with multifaceted catalytic properties for therapeutic applications remain underexplored. Here, we present two-dimensional BiCuSeO nanosheets (BCSO NSs) as the superlattice nanocatalyst for multimodal energy transformation-driven nanocatalytic therapy. Benefiting from the intrinsic layered heterostructures and a narrow bandgap, BCSO NSs feature photothermoelectric and sono-piezoelectric catalytic effects, as well as enzyme-mimicking catalytic activities. Theoretical calculations reveal that the internal electric fields within superlattice nanostructures contribute to the rapid separation and suppressed recombination of charge carriers. Consequently, BCSO NSs enable controlled reactive oxygen species generation under the second near-infrared light or ultrasound irradiations. The enzymatic activity of BCSO NSs also facilitates the transformation of tumor-specific substrates, dysregulating the redox homeostasis. The photothermoelectric and sono-piezoelectric/enzymatic activities of BCSO NSs have been exemplified by antibacterial and anticancer applications, highlighting the potential of two-dimensional superlattice nanocatalysts to address diverse pathological abnormalities.